2018
DOI: 10.12659/msm.909226
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Estimating Low-Density Lipoprotein (LDL) Levels: Total Cholesterol and Non-High-Density Lipoprotein (HDL) Can Be Used to Predict Abnormal LDL Level in an Apparently Healthy Population

Abstract: BackgroundWe aimed to predict the abnormal LDL level by using TG, TC, HDL, and non-HDL in this study.Material/MethodsTriglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) data were obtained from the Laboratory Information System (LIS) for 4 years (Oct 1, 2013 to Sept 30, 2017) from among 34 270 healthy Chinese patients at Shuyang People’s Hospital. TG, TC, HDL, and LDL (direct clearance method) were measured using a TBA2000FR biochemical analyzer. The non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The optimal TC levels suggested differed from Zhang et al [19] which suggested an optimal threshold at 182.5 mg/dL for detection of the abnormal LDL-C level (LDL-C ≥ 130 mg/dl) in apparently healthy populations. However, the study by Zhang only had access to laboratory results and did not have access to past medical history and physical examination, which may not be generalizable to healthy populations or those with low cardiovascular risks.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The optimal TC levels suggested differed from Zhang et al [19] which suggested an optimal threshold at 182.5 mg/dL for detection of the abnormal LDL-C level (LDL-C ≥ 130 mg/dl) in apparently healthy populations. However, the study by Zhang only had access to laboratory results and did not have access to past medical history and physical examination, which may not be generalizable to healthy populations or those with low cardiovascular risks.…”
Section: Discussionmentioning
confidence: 76%
“…While TC levels may not reflect the true risk of cardiovascular risk from dyslipidemia, however, implementation as a screening tool in low to medium income countries could help reduce the expense of screening and increase accessibility at a population level [19]. As previously stated, the price of TC test is two-times lower than price of LDL-C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid parameters -High-density lipoprotein cholesterol (HDL-C), Triglycerides and Total cholesterol (TC) were analyzed using the enzymatic method employed by the kits [14]. Low-density lipoprotein cholesterol (LDL-C) was calculated by the use of the Friedewald equation [15]. Fasting plasma glucose was determined using enzymatic oxidation in the presence of glucose oxidase, urea by the Urease-Berthelot method, uric acid by enzymatic colourimetric method and creatinine by the modified Jaffe Method [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (10 ml) were collected from each individual following overnight fasting for 12 h. Serum was obtained by centrifugation at 8,000 x g for 15 min at 4˚C. Total serum levels of triglyceride, cholesterol, low-density lipoprotein (LDL) cholesterol and high-density lipoprotein (HDL) cholesterol were measured using a TBA2000FR biochemical analyzer (Toshiba Corporation) as described previously (30). Metabolism of Gd 2 O 3 -EPL was then determined using inductively coupled plasma mass spectrometry (ICP-MS; Elan DRC II; PerkinElmer, Inc.) according to a previous study (31).…”
Section: Participantsmentioning
confidence: 99%